Pengaruh Likuiditas, Leverage, dan Non Performing Financing, Terhadap Stabilitas Keuangan pada Bank Umum Syariah di Indonesia Periode Tahun 2020-2024 - Rahman, Nabilli; Musthofa, Ujang Hanief; Nurmalia, Gustika (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the influence of liquidity (FDR), leverage (DER), and Non-Performing Financing (NPF) on the financial stability of Islamic Commercial Banks (BUS) in Indonesia (2020–2024) using panel data from 10 BUS. The Chow test and Hausman test determined the Fixed Effects Model (FEM) as the best model. The results show: FDR and NPF have no statistically significant effect. Meanwhile, DER has a positive and significant influence with a p-value of 0.009, as Sharia-compliant debt for productive financing through risk-sharing schemes enhances stability. The adjusted R² (11.39%) indicates limited explanatory power, with 88.61% attributed to external factors. From an Islamic perspective, this study highlights that the role of Islamic banks is not solely about financial achievement but also a manifestation of their social responsibility in building a more inclusive and sustainable economy aligned with Islamic values.